Prognostic significance of stromal сomponent in prostate cancer. - Yakovtsova, I. I.; Tkachenko, P. V.; Dolgaya, O. V.; Ivachno, I. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Stroma is a crucial factor in the growth and progression of prostate cancer. However, the morphological and molecular biological signs of cancer stroma that define prognosis of the disease have been investigated insufficiently. Objective. To identify relationships between morphological, immunohistochemical (vimentin, smooth muscle actin-α, MMP-9, collagen type IV) characteristics of the cancer stroma and criteria of aggressive clinical behavior, the risk of recurrence of prostate cancer. Metods. Stroma of the tumors was quantified in 112 patients treated with radical prostatectomy for clinically localized prostate carcinoma. Cancers were divided into three risk groups. Immunohistochemical study was conducted on the material of 33 cases of prostate cancer, 10 cases of normal prostate and 11 cases of atypical hyperplasia, in total 54 cases. The 2 test and Spearman rank correlation coefficient where used to compare the studied features. Results. Desmoplasia of prostate cancer occurred in 61.6% of cases, low, moderate and high grade in 29.5%, 25.9% and 6,2% respectively. Expression of vimentin, smooth muscle actin-α, MMP-9, collagen type IV in the cancer stroma where not uniform. Conclusion. Decrease of differentiation of prostate cancer from G1 to G2 was associated with increased degree of tumor desmoplasia, identified tendency to reduce desmoplasia level with decreasing differentiation to G3. Also revealed, the less differentiated tumor, the more expressed peritumoral reactive fibrosis. Absence of desmoplasia typical for low-risk prostate cancer, moderate and severe desmoplasia associated with cancers of the intermediate risk group. Stroma of prostate cancer with decreasing of tumor differentiation and growth of aggressive clinical behavior characterized by the disappearance of the collagen type IV, tendency to decrease smooth muscle actin-α and increase expression of vimentin because of increasing the number of tumor-associated fibroblasts and myofibroblasts. In the stromal cells with decreasing differentiation of prostate cancer and increasing the risk of recurrence has tended to increase of MMP-9 expression.